Improved direct measurement of the parity-violation parameter Ab using a mass tag and momentum-weighted track charge. - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2003)
We present an improved direct measurement of the parity-violation parameter A(b) in the Z boson-b-quark coupling using a self-calibrating track-charge technique applied to a sample enriched in Z-->bb events via the topological reconstruction of the B hadron mass. Manipulation of the Stanford Linear Collider electron-beam polarization permits the measurement of A(b) to be made independently of other Z-pole coupling parameters. From the 1996-1998 sample of 400,000 hadronic Z decays, produced with an average beam polarization of 73.4%, we find A(b)=0.906+/-0.022(stat)+/-0.023(syst).